The Effect of Implementing the Introduction to School Fields on Students' Teaching Ability - Indayani, Indayani; Hafid, Radia; Mahmud, Melizubaida; Sudirman, Sudirman (Lembaga Penelitian dan Pendidikan Mandala, 2023)
This study aims to determine the effect of implementing school introduction and orientation toward students’ teaching ability in the class of 2018, Economic Education Departement, Faculty of Economics, Universitas Negeri Gorontalo. This research uses a quantitative approach and explanatory research methods by taking primary data from the distribution of questionnaires to students in Economic Education, Class of 2018, Universitas Negeri Gorontalo. The number of sampling in this study is 43 respodents, and the data analysis technique uses simple linear regression. The result show that school introduction and orientation influence the teaching ability of students in the class of 2018 Economic Education Departemen, Faculty of Economics, Universitas Negeri Gorontalo. The influence amount reaches 40.6%, and the rest unexamined variabels influence 59.4%.